2016
DOI: 10.3389/fpls.2016.01770
|View full text |Cite
|
Sign up to set email alerts
|

Bradyrhizobium Inoculants Enhance Grain Yields of Soybean and Cowpea in Northern Ghana

Abstract: This study evaluated the symbiotic effectiveness and economic evaluation of Rhizobium inoculants with the objective of recommending the most effective inoculant strain for soybean and cowpea production in Northern Ghana. Field experiments were established in three locations using randomized complete block design with five blocks. A total of four treatments (Legumefix, Biofix, 100 kg N ha-1 and uninoculated control for soybean and BR 3267, BR 3262, 100 kg N ha-1 and uninoculated control for cowpea) were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
85
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 27 publications
14
85
0
2
Order By: Relevance
“…It was also interesting to observe that flower, pod, and seed production were not enhanced at their maximum by McL or McH, but by PpL alone or in combination with Mc. Ulzen [31] reported no increase in shoot biomass after inoculation with rhizobia on soybean and cowpea, and similar results were reported by Albareda [32]. Simultaneously, there was a consistent negative correlation among the four reproduction values in all but one (BmH + PpH + McH) treatment.…”
Section: Discussionsupporting
confidence: 79%
“…It was also interesting to observe that flower, pod, and seed production were not enhanced at their maximum by McL or McH, but by PpL alone or in combination with Mc. Ulzen [31] reported no increase in shoot biomass after inoculation with rhizobia on soybean and cowpea, and similar results were reported by Albareda [32]. Simultaneously, there was a consistent negative correlation among the four reproduction values in all but one (BmH + PpH + McH) treatment.…”
Section: Discussionsupporting
confidence: 79%
“…The increase in grain yield due to Bradyrhizobia inoculation may be attributed to the effectiveness of the inoculant in fixing N thereby meeting the nutrient requirement of the plant (Nyoki and Ndakidemi, 2013). Ulzen et al (2016) also observed a significant increase in grain yield of cowpea after inoculation with Bradyrhizobium inoculant.…”
Section: Grain Yieldmentioning
confidence: 68%
“…They studied the effect of rhizobia inoculation in different soil types under well-watered condition and concluded that rhizobia were ineffective to improve biomass production and the number of nodules. Ulzen et al [61] reported contrasting responses of rhizobia inoculation in two sites inoculated even with the same strains under rainfall condition and concluded that the non-response of rhizobia at Nyagli site was due to the lower native number of strains and other unknown factors. Furthermore, some previous studies found that cowpea inoculated with two glums species did not significantly affect leaf gas exchange under the volumetric soil water content around 8% [62].…”
Section: Discussionmentioning
confidence: 99%